Clustered randomized controlled trial protocol of a Mobility-as-a-Service app for College campuses. (June 2022) - Merlin, Louis A.; Freeman, Katherine; Renne, John; Hoermann, Serena
Highlights: We present a detailed protocol for a cluster randomized control trial (cRTC) in transportation. Randomized control trials (RCTs) and RCT protocols are still rare in the field of transportation. The trial crosses three south Florida colleges where large proportions of students commute. Intervention students receive the free U-RIDE app to help them plan alternative travel options. We discuss the complications of planning a RCT in a real-world campus environment. Abstract: This paper presents a protocol for a clustered, randomized controlled trial (RCT) in transportation planning. RCTs are still unusual in transportation planning, and this is the first RCT transportation protocol we are aware of seeking publication in a peer-reviewed journal. The trial tests a mobility-as-a-service app aimed at shifting mode choice to campus among an intervention student population while also tracking in parallel the mode choices of the control group. The concept behind the intervention is to leverage information and marketing to shift students' intentions relative to their travel to campus, following Azjen's Theory of Planned Behavior. The app, which is custom developed under the guidance of the research team, facilitates students' trips to campus by transit, biking, walking, and ride-hailing. An intended secondary outcome of the intervention is improved academic outcomes among students in the intervention group. The research team developed the protocol through a literature review of campus-based travel demand management measures, then by vetting a draft protocol with an expert panel, and then through a series of survey pilots. The advent of COVID- 19 in the middle of the research project demonstrated the challenges of planning a real-world RCT where researchers have limited ability to control exogenous factors.